Leisure identities and interactions - Kelly, John R. (Abingdon, Ox : Routledge, 2019)
First published in 1983. Leisure has too often been approached as a set of activities that people do when everything important has been completed. This text provides a different analysis demonstrating the centrality of leisure to human development and to important relationships. In Leisure Identities and Interactions the author analyses leisure in the context of role changes through the life course, but also as a social context in which we work out the identities that express who we really want to be. His focus is on the kinds of leisure that are both most common and most significant face-to-face encounters, family interaction, and episodes found in the midst of our roles and routines.
Preface -- 1. Meanings of Leisure: An Introduction; Part One: Styles of Leisure: Variety and Meaning -- 2. Variations in Leisure Styles -- 3. Life Course Changes -- 4. Personal and Social Identities -- Part Two: Social Contexts of Leisure -- 5. Leisure and the Family -- 6. Face-to-Face Interaction -- 7. Leisure Planning and Provision -- 8. Leisure Interaction and the Social Dialectic -- Index.
Includes index.
Keywords: LEISURE -- SOCIAL ASPECTS